Analisis Karakteristik dan Model Pendidikan Islam Jami’atul Washliyah : Analysis of Characteristics and Model of Islamic Education of Jami'atul Washliyah - Madani, Pattika Reyhan; Abbas, Ngatmin (ISEDU : Islamic Education Journal, 2024)
This study aims to analyze the objectives, characteristics, and educational models implemented by Jami’atul Washliyah in Indonesia. Jami’atul Washliyah is one of the largest Islamic organizations in Indonesia, playing a significant role in the development of Islamic education. This research employs a qualitative method with a descriptive analytical approach, examining various documents and literature. The findings show that the primary goal of Jami’atul Washliyah’s education is to shape individuals with noble character, deep religious knowledge, and the ability to contribute positively to society. The main characteristics of education at Jami’atul Washliyah include the integration of religious and general education, the application of Islamic values in all aspects of education, and an emphasis on moral and ethical development. The educational model implemented includes an integrated curriculum, extracurricular activities that support character development, and intensive religious training. These findings are expected to contribute to the development of Islamic education in Indonesia and serve as a reference for other educational organizations.